A COMPREHENSIVE REVIEW ON THE APPROACHES AND APPLICATIONS OF NANOPARTICLES - Molmoori, Rajkumar; Shriramoju, Anuradha; Chinnala, Krishna Mohan (International Journal of Pharma and Bio Sciences, 2026)
Nanoparticles have emerged as a cornerstone of modern science and technology, offering unique physicochemical properties that differ significantly from their bulk counterparts. Their nanoscale dimensions confer high surface area, tunable morphology, and enhanced reactivity, enabling diverse applications across medicine, energy, and environmental sectors. This review comprehensively discusses the major approaches employed in nanoparticle synthesis, including top‑down and bottom‑up techniques such as mechanical milling, sol‑gel processing, chemical reduction, and biological synthesis. Functionalization strategies-through surface modification, ligand attachment, and polymer coating-are highlighted for their role in improving stability, biocompatibility, and targeted delivery. Characterization methods like dynamic light scattering (DLS), transmission electron microscopy (TEM), and zeta potential analysis are examined to elucidate particle size, shape, and surface charge, which critically influence performance. The review further explores applications ranging from drug delivery and diagnostics to catalysis, imaging, and environmental remediation. In biomedical contexts, nanoparticles enable controlled release, site‑specific targeting, and enhanced therapeutic efficacy, while in energy systems they contribute to improved solar cells, batteries, and sensors. Environmental uses include pollutant removal and water purification. Overall, the integration of advanced synthesis and characterization techniques continues to expand the functional versatility of nanoparticles, positioning them as indispensable tools in sustainable technological innovation.